Pengaruh Kualitas dan Kepuasan Layanan Terhadap Loyalitas Konsumen di KFC Jl.Sudirman Yogyakarta - , AISHA KARIMAWATI; , Yulia Arisnani, MBA., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Consumers consume not only the tangible product but also service, which is intangible. In dinamic and competitive business environment, service quality become very important variable in determining the success of a business. Service quality will lead to customer satisfaction which later generates customer loyalty. The purpose of this study is to examine the effect of companyâs service quality and customer satisfaction on customer loyalty in service that use KFC Jl.Sudirman Yogyakartaâs customers as the respondents. The research method applied is survey. This research proves that service quality has both the direct and indirect effect to loyalty with or without satisfaction. According to the simple regression analysis, service quality has impact on satisfaction, satisfaction has impact on loyalty, and service quality has a direct impact on loyalty. In descriptive statistic, tangibles found as the highest score item from five construct of service quality (SERVQUAL), and responsiveness as the lowest score item.